Seasonal and diurnal water vapour distribution in the Sahelian area from microwave radiometric profiling observations. (13th May 2015) - Louf, Valentin; Pujol, Olivier; Sauvageot, Henri; Riédi, Jérôme
Abstract : This article deals with the tropospheric water vapour distribution at Niamey (Niger) observed with a high‐temporal‐resolution (14 s) microwave radiometric profiler. Data were collected during the whole year 2006 in the framework of the African Monsoon Multidisciplinary Analysis (AMMA) campain. Two seasonal periods are considered: the dry season, when the northeasterly Harmattan is flowing at low tropospheric level, and the wet season, associated with the southwesterly monsoon circulation. The fine vertical structure of temperature, convective air stability and water vapour for each seasonal period is described in detail and differences are emphasized. Typical temporal series and monthly averaged diurnal cycles are presented. It is shown that a diurnal cycle of water vapour is present throughout the year, including the dry season. The diurnal cycle of water vapour is controlled mainly by the nocturnal low‐level jet (NLLJ). During the dry season, the diurnal cycle of water vapour is organized into two layers: a lower layer (LL) from the surface up to 0.6–1.4 km above ground level (agl) and an upper layer (UL) from 1.4 up to 5–6 km agl. The water vapour distributions in the LL and UL are anticorrelated, with a half‐day temporal shift. As a result, the vertically integrated water vapour (IWV), which displays a quasi‐sinusoidal diurnal cycle when computed separately for the LL and UL, appears almost flat for the total tropospheric height, due to the half‐day period shift. This structure of two layers is not observed during the wet season. Probability density functions (pdfs) of water vapour content are presented. In dry conditions, the pdfs are well fitted by a log‐normal distribution, while the Weibull distribution fits the pdfs for wet conditions better.